Determination of (4E, 6E, 12E)-Tetradecatriene-8, 10-diyne-1, 3-diyl Diacetate in Rat Plasma and Tissues by HPLC-UV Method and Their Application to a Pharmacokinetic and Tissue Distribution Study. (24th February 2014) - Huo, Yan; Liu, Yu-Qiang; Bai, Zhong-Xu; Cai, Qian
Abstract : In China Atractylodis Rhizoma is widely used for the treatment of rheumatic diseases and digestive disorders. Stir-frying with wheat bran is the most common processing method. In order to clarify the influence of processing on pharmacological properties of Atractylodis Rhizoma, an investigation was carried out to compare the pharmacokinetics and tissue distribution of typical constituent after oral administration of raw Atractylodis Rhizoma and processed ones. A simple, rapid, and sensitive high performance liquid chromatography with UV detection was developed and validated for the determination of (4 E, 6 E, 12 E )-tetradecatriene-8, 10-diyne-1, 3-diyl diacetate in rat plasma. A chromatography was carried out on Diamonsil C18 (250 × 4.6 mm; 5 μ m) analytical column, using a mobile phase which consisted of acetonitrile and 0.1% phosphoric acid water (60 : 40, v/v) at a flow rate of 1.0 mL·min −1 . The wavelength was set at 336 nm. The LLOQ of (4 E, 6 E, 12 E )-tetradecatriene-8, 10-diyne-1, 3-diyl diacetate was 0.00143 μ g·mL −1 . Both accuracy and precision were satisfactory. The pharmacokinetic results showed that the T max ⁡ was 1 hour in advance and the C max ⁡ was increased after processing. Tissue distribution showed that the highest level was in spleen. And the concentrations in the spleen were increased after stir-frying with bran.